VAS and ESG score: a correlational analysis of oil companies listed on B3 - Porto, Giovana Fernandes; Vianna, Dilo Sergio de Carvalho; Queiroz, Juliana Molina; Lopes, Weslei Camelo; Carmo, Liege Moraes do (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: This study aims to analyze the relationship between value distribution indicators reported in the Value Added Statement (VAS) and ESG scores of Brazilian oil and gas companies listed on B3, covering the period from 2018 to 2022. Methodology: The research is classified as descriptive, documentary, and quantitative. Data were collected from companies’ financial statements and the Refinitiv Eikon database. The analysis was conducted using descriptive statistics, Pearson and Spearman correlation tests, and multiple linear regression models, including control variables related to firm size, leverage, and financial performance. Results: The results indicated statistically significant associations in bivariate analyses, particularly in the environmental and social dimensions, which proved to be more limited when examined in multivariate models. A positive relationship was identified between internally generated value and ESG performance, as well as between value distribution to government and ESG indicators. Conversely, value distribution to shareholders showed a negative relationship with ESG scores. No significant associations were found between VAS indicators and the governance dimension. Contributions of the Study: This study contributes to the literature by integrating accounting-based value distribution metrics with ESG indicators, grounded in stakeholder, legitimacy, and voluntary disclosure theories. Additionally, it advances empirical research by focusing on a high environmental impact sector, providing evidence that may support managers and investors in understanding the interaction between financial performance and sustainability practices.